2003
DOI: 10.1128/jb.185.3.860-869.2003
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Dialkylresorcinol Biosynthesis in Pseudomonas aurantiaca : Novel Head-to-Head Condensation of Two Fatty Acid-Derived Precursors

Abstract: 2-Hexyl-5-propylresorcinol is the predominant analog of several dialkylresorcinols produced by Pseudomonas aurantiaca (Pseudomonas fluorescens BL915). We isolated and characterized three biosynthetic genes that encode an acyl carrier protein, a ␤-ketoacyl-acyl carrier protein synthase III, and a protein of unknown function, all of which collectively allow heterologous production of 2-hexyl-5-propylresorcinol in Escherichia coli. Two regulatory genes exhibiting similarity to members of the AraC family of transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 52 publications
0
58
2
4
Order By: Relevance
“…The biosynthetic mutant genes DdarA and DdarB and the derivative mutant in gacS showed a complete loss of HPR production. The derivative mutant of the biosynthetic gene darC showed antifungal activity, likely reflecting the function of darC, a carrier of acyl intermediates during fatty acid synthesis (Byers & Gong, 2007), determined through the complementation of similar proteins inside the cell (Nowak- Thompson et al, 2003). Moreover, the transcriptional regulators darS and darR reduce HPR production, but only to half of the amount produced in the WT strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthetic mutant genes DdarA and DdarB and the derivative mutant in gacS showed a complete loss of HPR production. The derivative mutant of the biosynthetic gene darC showed antifungal activity, likely reflecting the function of darC, a carrier of acyl intermediates during fatty acid synthesis (Byers & Gong, 2007), determined through the complementation of similar proteins inside the cell (Nowak- Thompson et al, 2003). Moreover, the transcriptional regulators darS and darR reduce HPR production, but only to half of the amount produced in the WT strain.…”
Section: Discussionmentioning
confidence: 99%
“…auranthiaca BL915. In this strain, the genes responsible for HPR production are located in a cluster containing three presumptive biosynthetic genes (darA, darB and darC), followed by two independent sequences homologous to the regulatory genes from the AraC/XylS family (darS and darR; Nowak- Thompson et al, 2003). This dar cluster has recently been identified in P. chlororaphis PCL1606 (Calderó n et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We designated this region to be the bartoloside (brt) gene cluster (GenBank: KR059027). In contrast to previously characterized darAB-containing gene clusters, [10][11][12] the brt cluster lacks a designated ACP, suggesting the use of a trans-acting ACP or ACP thioesters from fatty acid biosynthesis. The participation of acyl-CoA substrates is unlikely as cyanobacteria, including S. salina LEGE 06155, lack a canonical β-oxidation pathway.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 59%
“…In other bacteria, a ketosynthase (DarB) and a putative aromatase (DarA) have been shown to synthesize DAR scaffolds in a convergent process. [10] DarB catalyzes the head-to-head condensation of a β-ketoacyl acyl carrier protein (ACP) thioester with an α,β-unsaturated acyl ACP thioester, resulting in a dialkylcyclohexanedione carboxylic acid (carboxy-CHD). [11] DarA is thought to be an aromatase based on its in vivo activity in a heterologous host, [11] but has not been characterized in vitro.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Earlier studies have reported the production of various antifungal compounds including phenazine and its derivatives (i.e., 1-oxyphenazine, phenazine-1,6,dicarboxylate, and 2-hexyl-5-propyl-alkylresorcinol) by P. aurantiaca [4,18]. Recently, Mandryk et al [12] reported new antimicrobial compounds produced by this bacteria, having molecular formulas of C 18 H 36 NO (molecular weight 282.8; antibacterial activity) and C 20 H 31 O 3 (molecular weight 319.3; antifungal activity).…”
Section: Discussionmentioning
confidence: 99%